Genetic variation of highly pathogenic Indian porcine reproductive and respiratory syndrome viruses after introduction in 2013 - RAJKHOWA, T K; VANLALRUATI, C; SINGH, Y D; RAVINDRAN, R; ARYA, R S (The Indian Journal of Animal Sciences, 2018)
To study its possible link to pathogenicity, the genomic variation in full ORF5 and ORF7 genes, and their encoded proteins in 26 field HP-PRRSV isolates from three major HP-PRRS outbreaks occurred in India, since 2013 was analysed. Sequence analysis and phylogenetic tree revealed involvement of genetically different strain in each outbreak of India rather persistence of a single strain. Analysis and comparison of N protein amino acid sequences of HP-PRRSV with VR2332 revealed consistent mutation at position 15D to N or K and 46 K to R in all the HP-PRRSV. GP5 protein showed consistent mutations at 29 positions from that of VR2332. The potential Nglycosylation sites in GP5 was found variable from 4–5 with one additional N-glycan moiety around the neutralizing epitope B. However, the ‘decoy’ epitope A was found highly conserved in all the HP-PRRSV.